Penguatan Ketahanan Masyarakat Melalui Kewirausahaan Hijau Dalam Pengembangan Pariwisata Pedesaan di Desa Wisata Egon Buluk, Kabupaten Sikka, Provinsi Nusa Tenggara Timur - Michael Rudolfus sawu; Natalia Kristiani Tandafatu (Universitas Nusa Nipa Maumere, 2025)
Green entrepreneurship plays a crucial role, hence requiring the formulation of its development scheme in rural tourism. This research aims to investigate green entrepreneurship practices that contribute to the sustainability and resilience of the local community. The research adopts a qualitative method using an appreciative inquiry approach. In-depth interviews involve key informants such as village government, local communities and rural tourism practitioners. The data analysis technique employed is the stages of appreciative inquiry. The stages of appreciative inquiry are grounding, discovery, dream, and destiny. It examines the orientation of rural tourism product development, community resilience and stakeholder synergies to formulate an ideal development model. The study finds that local community demonstrates a strong commitment to preserving natural and cultural resources while utilizing rural tourism as a means of economic empowerment. Adaptive strategies of the community and entrepreneurial initiatives do not yet show significant development. Stakeholder synergy remains notably low in shaping the trajectory of green entrepreneurship. The implications of this research emphasize the importance of developing adaptive strategies and entrepreneurial initiatives such as eco-friendly community-based tourism projects. It is necessary to strengthen collaboration among stakeholders to enhance green entrepreneurship development.